[OP.4D.08] DISORDERED SLEEP BREATHING (SDB) IS THE MAJOR DETERMINANT OF NON-DIPPING AND NOCTURNAL HYPERTENSION IN KIDNEY TRANSPLANT PATIENTS. (September 2016) - Mallamaci, F.; Tripepi, R.; Versace, M.C.; Provenzano, F.; Mafrica, A.; Torino, C.; D'Arrigo, G.; Leonardis, D.; Tripepi, G.; Zoccali, C.
Abstract : Objective: In renal transplant patients, the prevalence of nocturnal hypertension by far exceeds that of hypertension as assessed by clinic, daytime, and average 24-hour ABPM and night-time systolic BP (SBP) and the night-day ratio but no other BP metrics are independently associated with IMT in this population (Transplantation 2015 Dec 17). BP during nighttime may provide information for the assessment of CV risk attributable to BP burden in renal transplant patients but the determinants of this phenomenon are still undefined in these patients. Design and method: We recorded 24h-ABPM and performed polysomnography in 215 clinically stable transplant patients. Major classical CV risk factors and CKD-specific risk factors (including phosphate, eGFR, proteinuria and C Reactive Protein) were measured alongside. Our primary goal was to identify the functional correlates of average BP during night-time and of the night/day ratio, a parameter quantifying the BP dipping phenomenon. Results: The Apnea-Hypopnea Index (AHI) exceeded 5 episodes/h in 56 patients and 15 episodes/h in 19. Thus, 17% of patients had mild-to-moderate SDB and 9% severe SDB. In unadjusted analyses, AHI was directly related with night-time SBP (r = 0.19, P = 0.005) and the night/day SBP ratio (r = 0.18, P = 0.01). AHI also associated with average 24h-SBP and DBP (both r = 0.14, P = 0.04). Furthermore, age, gender, BMI, diabetes, phosphate, C-Reactive Protein, and background CV comorbidities were all associated with AHI. In multiple regression analyses adjusting for these parameters as well as for average day-time SBP, Hb, and proteinuria, AHI remained related with average night-time SBP (beta = 0.10, P = 0.02) and with the night/day SBP ratio (beta = 0.17, P = 0.02). In these models, the AHI ranked as the strongest correlate of nigh-time SBP burden. These results did not change also forcing into the model immunosuppressive treatment. Conclusions: In stable transplant patients, sleep disordered breathing is the most powerful functional correlate of nocturnal BP. These relationships are independent of age and comorbidities, eGFR and proteinuria and likely represents irreversible effects of long-term past exposure to kidney failure on the central nervous system.